The advantages of sound localization and speech perception of bilateral electric acoustic stimulation. (February 2014) - Moteki, Hideaki; Kitoh, Ryosuke; Tsukada, Keita; Iwasaki, Satoshi; Nishio, Shin-Ya; Usami, Shin-Ichi
Abstract Conclusion: Bilateral electric acoustic stimulation (EAS) effectively improved speech perception in noise and sound localization in patients with high-frequency hearing loss. Objective: To evaluate bilateral EAS efficacy of sound localization detection and speech perception in noise in two cases of high-frequency hearing loss. Methods: Two female patients, aged 38 and 45 years, respectively, received bilateral EAS sequentially. Pure-tone audiometry was performed preoperatively and postoperatively to evaluate the hearing preservation in the lower frequencies. Speech perception outcomes in quiet and noise and sound localization were assessed with unilateral and bilateral EAS. Results: Residual hearing in the lower frequencies was well preserved after insertion of a FLEX24 electrode (24 mm) using the round window approach. After bilateral EAS, speech perception improved in quiet and even more so in noise. In addition, the sound localization ability of both cases with bilateral EAS improved remarkably.